PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM - Muthmainnah, Muthmainnah (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2023)
Stock price is a measure of investor interest to invest in a company. For companies, a benchmark of company valuation can increase the company's stock price. Therefore, the company needs to know whether the share price is determined by the company's financial kinerje. Financial performance used in Return on Assets (ROA) and Return on Equity (ROE) research. The purpose of the research is to examine whether the share price of LQ45 companies is determined by financial performance during 2018-2022 on the Indonesia Stock Exchange. This research is causal research and multiple linear regression was selected with the help of Eviews version 12. This research is proven to find that financial performance shows that simultaneously ROA and ROE have a significant influence on stock prices. Partially, Return on Assets (ROA) has a positive and significant effect on stock prices while Return on Equity (ROE) has no influence on stock prices. These means ROA is measured for financial performance.